Education and emancipatory processes in latin america: reflections from José Martí - Streck, Danilo Romeu (2010)
The article discusses the situation of coloniality in Latin America, and the role of education within the movement of emancipation. It is assumed that José Martí’s thought plays a paradigmatic role in understanding the multifaceted processes of emancipation. In this study his ideas will be articulated with the thought of Simón Rodríguez, Domingo Faustino Sarmiento, Frantz Tamayo, José Vasconcelos, among others. These authors agree with each other that the emancipatory processes left behind a sense of being unfinished. It is argued that revisiting the origins of emancipatory thinking in Latin America is important to recover a common memory and to work towards a shared destiny.